The effects of fumonisin and high protein dried distillers grain on pig growth performance - Rao, Zhong-Xing (Kansas State University, 2020)
Experiment 1 used a total of 350 pigs to determine the effects of increasing fumonisin concentration from 7.2 to 35.1 mg/kg on nursery pig growth performance and serum sphinganine (SA) to sphingosine (SO) ratio. Experiments 2 and 3 used a total of 650 pigs to determine the efficacy of various commercial products on growth performance and serum SA:SO ratios of nursery pigs fed high fumonisin diets. Experiment 4 used a total of 1,890 pigs to determine the effects of pigs fed diets with high-protein dried distillers grains (HPDDG) or conventional dried distillers grains with solubles (DDGS) on growth performance and carcass characteristics. Experiment 1 determined that increasing fumonisin concentration linearly reduced growth performance and final BW, and linearly increased serum SA:SO ratios. These results demonstrate that for 20- to 60-lb nursery pigs, diets containing greater than 32.7 mg/kg of fumonisin should be avoided, as increasing fumonisin concentration worsens growth performance and serum SA:SO ratio. In Exp. 2 and 3, growth performance and serum SA:SO ratios were improved in pigs fed high fumonisin diet with Biofix Select Pro, but not with Kallsil Dry or Feed Aid Wide Spectrum. The improvement in serum SA:SO ratios with Biofix Select Pro was only found in pigs fed 30 mg/kg of fumonisin (Exp. 3), but not 60 mg/kg (Exp. 2). In Exp. 4, there were no differences observed in ADG between pigs fed either DDG sources. Increasing either conventional DDGS or HPDDG decreased carcass yield and HCW; however, there were no differences between pigs fed HPDDG or conventional DDGS. Iodine value (IV) increased with increasing either DDG sources, and was greater in pigs fed HPDDG than conventional DDGS, which was probably due to the difference in oil content.
Keywords: Growing-finishing pigs; Nursery pigs; Fumonisin; High protein dried distillers grain